K.H. Abdurrahman Wahid’s (Gus Dur) Principle Ideology And Post-National Tragedy Multicultural Education Building: An Educational System Perspective - Rohanah Hidayati, Titiek (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This paper can be said to be an enrichment of the study of multicultural education which has been discussed for a long time in Indonesia, by presenting a new character who has never actually made multicultural education his idea of thought. Gus Dur’s existence is more of an ideology of multicultural thought. Because of that, this paper is more formed on the reconstructive process of Gus Dur’s thinking in general in terms of Islam, culture, and ideological discourse in Indonesia, which is contextualized in the world of education. Besides that, the implementation of this paper will also be designed through a system theory approach in the world of education. So that non-specific thoughts become more practical and can be used as a strategy for teachers in carrying out their learning in educational institutions. Finally, based on this research, the most important lesson from Gus Dur’s cultural thinking and ideological attitude, to build multiculturalism-based education in Indonesia, lies in Gus Dur’s strong principle that Bhinneka Tunggal Ika is a people’s identity that cannot be changed by any political power, Pancasila as the ideology that must be understood and lived by all levels of society in Indonesia, and adhere to the rules of the nation and state in Indonesia whether through integrative cultural and religious values that live in the Unitary State of the Republic of Indonesia and the substance content of the 1945 Constitution, that embraces all groups without discriminating against SARA.